An Islamic perspective on decision making under uncertainty - Muhammad Sri Wahyudi Suliswanto (Prodi Magister Ekonomi Syariah FEBI UIN Walisongo Semarang, 2021)
Purpose – The purpose of this study is to find out the Islamic view regarding decision making in uncertainty.Method – The method used is literature study from various related references.Result – The result of this study is that uncertainty or risk is not something that is forbidden in Islam. Implication – The implication of this study is the advantage of Islamic economics which lies in recognizing this uncertainty. Very useful as a stimulant and motivation to